Penerapan Model PBL, TGT dan PAP Meningkatkan Aktivitas dan Hasil Belajar IPA Siswa Kelas 5 SD - Muhammad Rafli Ridha; Ramadi Ramadi (Lembaga Pengembangan Kinerja Dosen, 2023)
In this research, there were obstacles or problems with students' activities and learning outcomes in less than optimal science content. The reason is due to a lack of skills in gathering information, still using conventional approaches, and one-way learning. The proposed solution is to apply a combination model of PBL, TGT, and Picture and Picture. The purpose of this research was to determine the activities and learning outcomes of grade 5 students at SDN Teluk Tiram 2 Banjarmasin, of which there were 20 students, including 7 boys and 13 girls. This research applies the PTK method and also uses qualitative and quantitative approaches. Qualitative data was obtained from teacher and student observations, while quantitative data came from personal written tests to evaluate student learning outcomes. The research results showed that teacher activity at meeting 4 reached 94% with the criteria